2010
DOI: 10.1007/s12603-010-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Urban environment, physical inactivity and unhealthy dietary habits correlate to depression among elderly living in eastern Mediterranean islands: The MEDIS (MEDiterranean ISlands elderly) study

Abstract: The prevalence of depression is quite high between elderly people living in Greek islands and Cyprus. Urban environment that may also interact with sedentarism and unhealthy dietary habits seems to promote depression in the studied population. Efforts to lower the prevalence of depression in the elderly should target on the aforementioned factors that employ functional impairment, social environment and dietary habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 50 publications
4
60
0
3
Order By: Relevance
“…This result reflects a relatively high adherence of Greek fishermen to the traditional Greek Mediterranean diet if compared with the results of a study performed in almost all habitants of small borderline Greek islands of Aegean Sea (islands like Nisiros, Anafi, Patmos, Thymaina, Kasos, Agathonisi, Leipsoi, Fournoi, Tilos, and a part of Rodos island) which concluded that population of small borderline islands has been urbanised in terms of dietary choices, thus raising the consequences in terms of cardiovascular disorders and depression [16]. Alcohol consumption is found to be a daily habit for the present study's fishermen.…”
Section: Discussionmentioning
confidence: 99%
“…This result reflects a relatively high adherence of Greek fishermen to the traditional Greek Mediterranean diet if compared with the results of a study performed in almost all habitants of small borderline Greek islands of Aegean Sea (islands like Nisiros, Anafi, Patmos, Thymaina, Kasos, Agathonisi, Leipsoi, Fournoi, Tilos, and a part of Rodos island) which concluded that population of small borderline islands has been urbanised in terms of dietary choices, thus raising the consequences in terms of cardiovascular disorders and depression [16]. Alcohol consumption is found to be a daily habit for the present study's fishermen.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in elderly men and women, the consumption of fish, vegetables, olive oil, and cereal correlated negatively with the severity of depressive symptoms (Mamplekou et al, 2010). The benefits from fish and olive oil intake remained significant even when adjusted for confounders such as age, sex, education status, BMI and physical activity status, as well as the presence of a number of medical conditions.…”
Section: The Relationship Between Diet and Depressionmentioning
confidence: 97%
“…These findings could be explained in part by evidence that shows that females are more likely to be aware of healthy eating guidelines, and to report healthy eating behaviours, including consuming FV, than their male counterparts (71) . In addition, some studies found depression was associated with some varieties of FV but not with others (48,62,70,72) . A possible reason for this is that different varieties of FV have different nutritional compositions and hence may not be linked with psychological outcomes to the same extent.…”
Section: People's Perceptions Of Fruit and Vegetablesmentioning
confidence: 98%
“…Moreover, certain dietary patterns characterised by high intakes of FV, have been associated with a decreased prevalence of depression (67,68) . However, despite these positive findings, some studies have failed to produce evidence to support an association between either FV intake (69) or FV-rich dietary patterns (70) and depression. In fact, the majority of existing studies have reported heterogeneous results, either with regard to specific subsets of participants or types of FV.…”
Section: People's Perceptions Of Fruit and Vegetablesmentioning
confidence: 99%